The effect of soybean formula and formula 100 supplementation on the growth of preschool children - M Mexitalia; Yohanes Tri Nugroho; J C Susanto (Indonesian Pediatric Society Publishing House, 2016)
Background Preschool children are vulnerable in growth. Soy- bean formula (SF) and formula-100 (F100) are supplementary foods which contain of high energy and are available at low price; how- ever, they are not widely used for preschool children. Objectives To investigate the effect of SF compared to F100 on the growth of preschool children. Methods A cross-over trial was conducted on 96 preschool chil- dren aged 4-7 years. Subjects were randomly divided into 2 groups which received 200 ml soybean formula (n=49) or F100 (n=47) for 1 month and crossed-over after a six-week wash-out period. Body weight was measured weekly. Body height and food analysis by 3- day food recall were measured at the beginning and the end of the study. The criteria of the acceptability of the formula was either good or poor. Results Supplementation with SF as well as F100 induced catch up growth as shown by the increase of Δz-score. There were no significant difference of Δ weight for age z-score, Δ height for age z-score, and Δ weight for height z score between groups during the first and second phases of the trial. The acceptability of F100 was significantly better than that of SF at the beginning; neverthe- less, the difference was not significant at the second phase trial. Conclusions Soybean formula and F100 given for a one month period can induce catch-up growth in preschool children. Soybean formula as an alternative health food can be accepted by preschool children